Alkaline battery based on phenazine derivative
By using phenazine derivatives with side substituents as anode material, the short cycle life and stability problems of alkaline aqueous batteries in anode materials are solved, and the battery performance of high capacity, high power density and long cycle life is achieved. .
Patent Information
- Application Number
- CN202410726141.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-07
- Filing Date
- 2024-06-05
- Publication Date
- 2025-02-14
AI Technical Summary
The existing alkaline aqueous batteries have problems such as short cycle life, zinc oxidation and undesired passivation layer formation in the anode material, which affects their stability and application sustainability.
Develop an alkaline battery based on phenazine derivatives, using phenazine derivatives with 1 to 4 pendant substituents as the anode material, and combining appropriate electrolytes and structural designs to improve the cycling stability and electrical power of the battery Chemical properties.
A reversible capacity of at least 170mAh g-1 at 0.2A g-1, a power density of at least 20KW kg-1 at 10A g-1, and a stable cycleability of over 9000 cycles, significantly improving alkaline batteries performance.
Smart Images

Figure CN119447290A_ABST
Abstract
Description
CROSS-REFERENCE TO RELATED APPLICATIONS
[0001] This application claims priority to U.S. patent application No. 18 / 366,641, filed on August 7, 2023, and the disclosure of which is incorporated herein by reference in its entirety. Technical Field
[0002] The present invention generally relates to the field of electrochemistry or energy storage. More specifically, the present invention provides an alkaline battery based on phenazine derivatives. Background Art
[0003] Currently, researchers in this field are actively working to address the major challenges brought about by the depletion of fossil energy and environmental degradation by focusing on the development of renewable energy. Electrochemical energy storage technologies, such as organic lithium-ion batteries (LIBs), nickel metal hydride (MH) batteries, and lead-acid batteries are recognized as efficient energy storage devices for renewable energy. 1,2 .
[0004] Among these technologies, high energy density organic lithium-ion batteries (LIBs) have revolutionized the fields of portable electronics and electric vehicles. 3 However, incidents with LIBs have raised serious safety concerns, prompting the development of safe aqueous batteries for specific applications. 4 .
[0005] Alkaline aqueous batteries (ANAB) are intrinsically safe and have a potential high voltage 5,6,7 However, corrosion caused by side reactions under alkaline conditions is inevitable for anode materials, which leads to poor cycling stability of ANAB. 8 Cadmium metal has become the first generation anode material for alkaline aqueous batteries due to its high energy density, but it has been gradually eliminated in ANABs due to its toxicity and strong "memory" effect. Subsequently, research and practice have been carried out to explore and apply superstable alloys as alternative materials for cadmium metal in ANABs. 9 However, the low nominal cell voltage (1.2 V) and high cost of the alloy remain unsatisfactory.
[0006] Zinc (Zn) metal has been extensively studied in recent years due to its low redox potential (-1.24 V vs. standard hydrogen electrode (SHE)) and remarkably high theoretical specific capacity (820 mAh g -1 ) and become an ideal anode material for alkaline batteries 4,10,11 However, the relatively short cycle life caused by Zn oxidation and the formation of an undesirable Zn(OH)4 passivation layer has hindered the development of Zn as an anode material under alkaline conditions. 2,8,12 .
[0007] To date, few metal materials can operate stably in alkaline systems. To overcome these obstacles and achieve sustainable applications of alkaline batteries, it is crucial to design high-performance, low-cost and environmentally friendly anode materials for ABAN. In addition to metals, the design of promising anode materials for ABAN has been extended to organic molecular materials. Organic molecules offer advantages such as low toxicity, cost-effectiveness and structural diversity. At the same time, replacing metal anodes with organic electrode materials can potentially solve problems associated with metal anodes, such as dendrites, passivation and corrosion.
[0008] Quinone polymers have attracted much attention and been extensively studied as organic electrode materials for ABAN, which store charge through an "ion coordination" mechanism. These materials have been shown to be effective in various electrolyte systems, including Al 3+ 、Zn 2+ 、Li + 、H + and NH4 + Wide applicability in 13-16 However, the potential of these materials is much higher than that of the zinc anode, which results in low battery voltage and energy density.
[0009] Phenazine (PZ) derivatives have shown great promise as electrode materials due to their potential high cycling stability. 17,18 The highly electronegative nitrogen atom in the phenazine compound significantly affects the density distribution of the electron cloud in the ring, thereby transferring the electron density from the π system to the nitrogen atom. Compared with quinone compounds, phenazine derivatives with higher electron cloud density exhibit greater magnetoresistance to accepting electrons, which leads to a relatively low redox potential. 19-21 .
[0010] However, despite the lower redox potentials of phenazine derivatives compared to most organic compounds, their redox potentials are still significantly more positively polarized than that of zinc metal. Furthermore, the effect of grafted functional groups on the electrochemical redox properties of phenazine derivatives needs to be investigated. Summary of the Invention
[0011] Therefore, the present invention aims to address the challenges associated with alkaline batteries. Specifically, the present invention aims to develop a high-performance, low-cost, and environmentally friendly anode material for alkaline rechargeable batteries that overcomes issues such as short cycle life, zinc oxidation, and the formation of an undesirable passivation layer. Furthermore, the present invention investigates the effect of grafted functional groups on the electrochemical properties of phenazine derivatives.
[0012] In a first aspect, the present invention provides an alkaline battery based on a phenazine derivative, comprising an anode formed of a phenazine derivative having 1 to 4 side substituents; a cathode; a separator disposed between the cathode and the anode; and an electrolyte disposed in the space between the cathode and the anode. The alkaline battery based on a phenazine derivative exhibits a charge / discharge rate of 0.2 A g -1 At least 170mAh g -1 The reversible capacity at 10A g -1 At least 20KW kg -1 The power density is high, and the cyclability is stable over 9000 cycles.
[0013] According to one embodiment, the side substituent comprises an electron-donating group or an electron-withdrawing group, wherein the electron-donating group comprises an amino group, a hydroxyl group, or a combination thereof, or the electron-withdrawing group comprises a methyl group, a carboxyl group, or a combination thereof.
[0014] According to one embodiment, the anode and the cathode include a current collector, at least one active material, one or more conductive particles, and at least one binder.
[0015] According to one embodiment, the current collector comprises carbon nanotube paper, carbon cloth, and nickel foil.
[0016] According to one embodiment, the at least one active material comprises phenazine (PZ), 2-hydroxyphenazine (PZ-OH) and 1,2-dihydroxyphenazine (PZ-2OH).
[0017] According to one embodiment, the one or more conductive particles include carbon nanotubes, ketjen black and super
[0018] According to one embodiment, the at least one binder comprises sodium carboxymethylcellulose (CMC-Na), polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE).
[0019] According to one embodiment, the cathode comprises Ni(OH)2 and Pt / C.
[0020] According to one embodiment, the electrolyte comprises a solvent and a solute, wherein the solvent comprises deionized water, the solute comprises sodium hydroxide, potassium hydroxide, and lithium hydroxide, and the concentration of the solute is in the range of 1M to 6M.
[0021] Optionally, the phenazine derivative-based alkaline battery further comprises a graphene oxide (GO) membrane, which is assembled by inserting the GO membrane between the anode and the separator, and the electrolyte is added between the anode and the cathode. The GO membrane is formed by mixing an ethanol solvent and 2% to 3% GO by mass to obtain a suspension, filtering the suspension and drying it at 70°C for 24 hours. Finally, a self-supporting GO membrane is obtained by peeling the GO membrane from the filter paper.
[0022] According to one embodiment, the alkaline battery based on phenazine derivatives 40 mAh g -1 The high-rate capacity of the phenazine derivative-based alkaline battery retains at least 10% of the initial capacity, and the discharge potential of the phenazine derivative-based alkaline battery is lower than -0.8V.
[0023] According to another embodiment, increasing the number of electron donating side substituents results in a lower electron affinity and a lower redox potential.
[0024] In a second aspect, the present invention provides a method for preparing the phenazine derivative, comprising preparing at least one precursor comprising at least one benzene derivative, at least one phenylenediamine derivative, and a solvent; dissolving the at least one benzene derivative in the solvent to form a homogeneous solution A; mixing the at least one phenylenediamine derivative with the solution A to form a suspension; and filtering the suspension and washing the suspension with deionized water until the filtrate becomes colorless. The molar ratio of the at least one benzene derivative to the at least one phenylenediamine derivative is in the range of 1:1 to 1:0.8.
[0025] According to one embodiment, the method further comprises concentrating the mixture under reduced pressure and adding deionized water to obtain a suspension, followed by filtering and washing the suspension.
[0026] According to one embodiment, the at least one benzene derivative comprises benzoquinone or 2,5-dihydroxy-1,4-benzoquinone.
[0027] According to one embodiment, the at least one phenylenediamine derivative has the following chemical structure: wherein R1 and R2 are independently selected from H, Cl, COOH or CH3.
[0028] According to one embodiment, the solvent comprises ethanol, deionized water or a combination thereof.
[0029] According to another embodiment, the reaction temperature of the step of mixing the at least one phenylenediamine derivative with the solution A to form a suspension is in the range of -10°C to 100°C, and the reaction time is in the range of 5-10 hours.
[0030] This invention relates to an economical and environmentally friendly synthetic method for producing a range of pendant-substituted phenazine organic materials. The electrochemical potential of these organic materials can be tailored by varying the type and amount of pendant substitution. By incorporating electron-donating groups, such as amino and hydroxyl groups, the potential of phenazine derivatives can be lowered, enabling the development of ultra-low voltage, highly stable organic materials for alkaline electrochemical storage devices.
[0031] Compared with the prior art, the present invention provides the following main advantages: (1) The preparation method for phenazine derivatives is simple, uses low-cost raw materials, and the reaction process is environmentally friendly, which makes it beneficial for large-scale production. (2) The redox potential of the prepared phenazine derivatives can be tuned by changing the type and number of side functional groups, which opens up the possibility of applying phenazine derivatives in the energy field. (3) Phenazine derivatives with hydrophilic side groups exhibit excellent rate performance, which is attributed to the formation of hydrogen bonds between the hydroxyl groups and water molecules. These hydrogen bonds promote the H + Rapid transport within a material via the Grotthuss mechanism. (4) The phenazine derivatives exhibit ultra-low redox potential and ultra-high cycle stability in various alkaline battery systems, including alkaline nickel-based systems and alkaline air battery systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Embodiments of the present invention are described in more detail below with reference to the accompanying drawings, in which:
[0033] Figure 1A The molecular structures of three phenazine derivatives and the corresponding calculated ESP distributions are shown. Figure 1B The three phenazine derivatives are shown 1 H NMR spectroscopy. Figure 1C FT-IR spectra of three phenazine derivatives are shown. Figure 1D CV curves of three phenazine derivatives are shown. Figure 1E The three phenazine derivatives are shown in 1A g -1 Constant current discharge / charge curves at current density of . Figure 1F The calculated frontier molecular orbital energies and electron affinities of the three molecules are shown. Figure 1GComparison of discharge potentials between PZ-2OH and organic anodes in the reported base systems is shown;
[0034] Figure 2A Shows the PZ-OH 1 H NMR spectroscopy. Figure 2B Shows the PZ-2OH 1 H NMR;
[0035] Figure 3A Shown are the XRD curves of the synthesized phenazine derivatives. Figure 3B An optical photograph of the phenazine derivative thus synthesized is shown. Figure 3C shows a scanning electron microscope (SEM) image of the phenazine derivative thus synthesized;
[0036] Figure 4 TGA curves of three phenazine derivatives under N2 atmosphere are shown;
[0037] Figure 5 The optimized structures and calculated LUMO and HOMO energy levels of three phenazine derivatives are shown;
[0038] Figure 6A The rate performance of three phenazine derivatives at different current densities is shown. Figure 6B A schematic diagram showing the impedance spectrum of a battery is shown. Figure 6C The EIS curves of PZ, PZ-OH, and PZ-2OH molecules are shown. Figure 6D Plotting the real part of the impedance versus ω 1 / 2 The relationship between them. Figure 6E The ln(R ct ) versus 1000 / T Arrhenius plot. Figure 6F Schematic diagram showing the ion conduction mode in the hydrogen bonding network in PZ-2OH. Figure 6G shows the calculated RDG isosurface of PZ-2OH versus sign(λ2)ρ;
[0039] Figure 7 shows the Nyquist plot of PZ-2OH at different temperatures;
[0040] Figure 8 The CV curves at different scan rates and the corresponding log i values of PZ, PZ-OH, and PZ-2OH are shown. peak relative to log v;
[0041] Figure 9 The capacitance contribution ratios of three phenazine derivatives at different scan rates are shown;
[0042] Figure 10 The coefficients b of PZ, PZ-OH, and PZ-2OH are shown;
[0043] Figure 11 shows the SEM image of the GO film;
[0044] Figure 12A The GO||Ni(OH)2 battery is shown to be -1 The CV curve below. Figure 12B The GO||Ni(OH)2 battery is shown to be -1 The GCD curve below;
[0045] Figure 13A The CV curves of the PZ-2OH||Ni(OH)2 battery are shown. Figure 13B The rate performance and Coulombic efficiency at different current densities are shown. Figure 13C A comparison of the energy density and power density of the PZ-2OH||Ni(OH)2 battery with other energy storage systems is shown. Figure 13D A comparison of cell discharge voltages of organic electrode materials in acidic electrolytes, mild electrolytes, and alkaline electrolytes is shown. Figure 13E The results show that the PZ-2OH||Ni(OH)2 full battery has a temperature range of -30℃ to 20℃ and a -1 GCD curves at current density of . Figure 13F The PZ-2OH||Ni(OH)2 battery is shown to be -1 Cycle life at current density. Figure 13G A comprehensive performance evaluation between conventional Ni-based batteries (Zn||Ni, MH||Ni, Cd||Ni) and PZ-2OH||Ni(OH)2 is shown, including price, energy density, voltage, toxicity, and stability;
[0046] Figure 14 The price comparison of the prepared phenazine derivatives and other anode materials for alkaline nickel-based batteries is shown;
[0047] Figure 15A Shown are the GCD curves of PZ-2OH||Ni(OH)2 at different current densities. Figure 15B The CV curves of the PZ-2OH||Ni(OH)2 full cell at different scan rates are shown;
[0048] Figure 16 The linear fit of the peak current density of the PZ-2OH||Ni(OH)2 full cell with different scan rates is shown;
[0049] Figure 17A The PZ-2OH anode is shown to be -1 Charge / discharge curves at current density of . Figure 17B The complete spectrum of the PZ-2OH electrode at selected points is shown. Figure 17C High-resolution N1s spectra of the PZ-2OH electrode at selected points are shown. Figure 17D In situ Raman spectra of PZ-2OH during the charge and discharge processes are shown. Figure 17E Typical Raman spectra of the PZ-2OH electrode at the annotated points are shown. Figure 17F shows the ex situ FTIR of the PZ-2OH electrode after different cycles;
[0050] Figure 18 Scheme showing the redox reaction mechanism of the PZ-2OH anode;
[0051] Figure 19A A typical GCD curve of a PZ-2OH||air battery is shown. Figure 19B The rate performance of the PZ-2OH||air battery within a certain range of current density is shown. Figure 19C shows the cycling stability of the PZ-2OH||air battery; and
[0052] Figure 20 The PZ-2OH||air battery is shown at 5mV s -1 CV curves at a scan rate of . DETAILED DESCRIPTION
[0053] The present invention will be described in detail by way of the following examples and accompanying drawings. It should be understood that the specific examples are provided for illustrative purposes only and are not to be construed in a limiting sense. Those skilled in the art will appreciate that variations and modifications other than those specifically described may be made to the invention described herein.
[0054] The present invention includes all such variations and modifications. The present invention also includes all steps and features referred to or indicated in this specification, individually or collectively, and any and all combinations or any two or more of the steps or features. Other aspects and advantages of the present invention will be apparent to those skilled in the art from a review of the following description.
[0055] Alkaline aqueous batteries are inherently safe and have the potential for high voltage. Specifically, alkaline aqueous batteries have garnered significant research attention due to their high voltage, low cost, and excellent safety profile. However, conventional metal anode materials are susceptible to corrosion under alkaline conditions, resulting in poor cycling stability of alkaline aqueous batteries. Furthermore, conventional metal anodes used in alkaline electrolytes often exhibit poor stability and severe side reactions.
[0056] Organic materials present a promising solution for overcoming these challenges, offering potential solutions to problems such as dendrite formation, passivation, and corrosion of metal anodes. This is because organic materials are composed of non-metallic elements (such as C, H, O, N, and S), unlike inorganic materials. However, organic materials generally lack a sufficiently negative potential to function as anodes.
[0057] Therefore, the present invention provides an alkaline battery based on a phenazine derivative, comprising an anode formed of a phenazine derivative having 1 to 4 side substituents; a cathode; a separator disposed between the cathode and the anode; and an electrolyte disposed in the space between the cathode and the anode. The alkaline battery based on a phenazine derivative exhibits a charge / discharge rate of 0.2 A g -1 At least 170mAh g -1 The reversible capacity at 10A g -1 At least 20KWkg -1 The power density is high, and the cyclability is stable over 9000 cycles.
[0058] Phenazine (PZ) derivatives are promising electrode materials due to their potential for high cyclic stability. Although their redox potentials are lower than those of most organic compounds, they are still significantly positive to that of zinc metal. It has been found that the introduction of hydroxyl groups can effectively lower the redox potential of organic materials by approximately 0.4 V. Furthermore, the redox kinetics of the materials are significantly enhanced by the formation of fast ion transport channels through intramolecular hydrogen bonding.
[0059] In one embodiment, the side substituents can be electron donating groups or electron withdrawing groups. Electron donating groups include but are not limited to amino groups, hydroxyl groups, or combinations thereof, or electron withdrawing groups include but are not limited to methyl groups, carboxyl groups, or combinations thereof.
[0060] In one embodiment, the anode material of the phenazine derivative-based alkaline battery is phenazine or hydroxyl-substituted phenazine, including but not limited to phenazine (PZ), 2-hydroxyphenazine (PZ-OH) and 1,2-dihydroxyphenazine (PZ-2OH).
[0061] These phenazine derivatives have varying numbers of hydroxyl groups. Comprehensive studies have demonstrated that hydroxyl-substituted groups adjacent to phenazine can lower the redox potential by reducing the ability to lose electrons and improve rate performance by forming hydrogen bonds with water molecules in the electrolyte. Furthermore, phenazine derivatives with hydroxyl groups provide fast charge transfer pathways through intermolecular interactions of the hydroxyl functional groups, which reduce charge transfer impedance and yield superior rate performance compared to phenazine.
[0062] In one embodiment, the cathode material may be Ni(OH)2 or Pt / C.
[0063] Preferably, the alkaline battery of the present invention may be a PZ||Ni(OH)2 battery, a PZ-OH||Ni(OH)2 battery or a PZ-2OH||Ni(OH)2 battery.
[0064] In one embodiment, the introduction of a hydroxyl group into phenazine, which acts as an electron donor group, can significantly reduce the discharge potential, for example, from -0.78 V (PZ) to -1.07 V (PZ-2OH).
[0065] In one embodiment of the present invention, the anode and cathode may include a current collector, at least one active material, one or more conductive particles, and at least one binder. The current collector includes, but is not limited to, carbon nanotube paper, carbon cloth, and nickel foil. The at least one active material includes, but is not limited to, PZ, PZ-OH, and PZ-2OH. The one or more conductive particles include, but are not limited to, carbon nanotubes, Ketjen black, and super The at least one binder includes, but is not limited to, CMC-Na, PTFE, and PVDF.
[0066] In one embodiment, the electrolyte comprises a solvent and a solute, wherein the solvent may be deionized water, and the solute may be sodium hydroxide, potassium hydroxide, or lithium hydroxide, and the concentration of the solute is in the range of 1M to 6M.
[0067] Optionally, the phenazine derivative-based alkaline battery further comprises a graphene oxide (GO) membrane, the phenazine derivative-based alkaline battery is assembled by inserting the GO membrane between the anode and the separator, and the electrolyte is added between the anode and the cathode.
[0068] In one embodiment, the present invention can improve the battery capacity and energy density of alkaline batteries. For example, alkaline batteries based on phenazine derivatives show a high energy density at 0.2 A g -1 At least 170mAh g -1 High reversible capacity at 10A g -1 At least 20KW kg-1 High power density and excellent stable cyclability of more than 9000 cycles.
[0069] More preferably, the optimized PZ-2OH||Ni(OH)2 battery exhibits a high -1 208mAh g -1 High capacity (anode), 247Wh kg -1 High energy density (anode), at 10A g -1 26.2KW kg -1 The battery features high power density, excellent cycling stability of over 9000 cycles and a low capacity decay rate of approximately 0.075% per cycle.
[0070] In one embodiment, the discharge potential of the phenazine derivative-based alkaline battery is lower than -0.8 V. For example, the discharge potential may be -0.85 V, -0.9 V, -0.95 V, or -1.00 V.
[0071] In one embodiment, an alkaline battery based on a phenazine derivative 40 mAh g -1 The high rate capacity of the device retains at least 10% of the initial capacity. For example, the initial capacity retains at least 11%, at least 12%, at least 13%, at least 14%, at least 15%, at least 16%, at least 17%, at least 18%, at least 19%, or at least 20%.
[0072] Preferably, the phenazine derivative-based alkaline battery retains 20% of its initial capacity.
[0073] In one embodiment, the present invention also demonstrates the feasibility of using PZ-2OH in an alkaline PZ-2OH||air battery, thereby further confirming its applicability under alkaline conditions.
[0074] In another aspect, the present invention provides a method for preparing the phenazine derivative, comprising preparing at least one precursor comprising at least one benzene derivative, at least one phenylenediamine derivative, and a solvent; dissolving the at least one benzene derivative in the solvent to form a homogeneous solution A; mixing the at least one phenylenediamine derivative with the solution A to form a suspension; and filtering the suspension and washing the suspension with deionized water until the filtrate becomes colorless. The molar ratio of the at least one benzene derivative to the at least one phenylenediamine derivative is in the range of 1:1 to 1:0.8.
[0075] In one of the embodiments, the at least one benzene derivative includes, but is not limited to, benzoquinone or 2,5-dihydroxy-1,4-benzoquinone.
[0076] In one of the embodiments, the at least one phenylenediamine derivative has the following chemical structure: wherein R1 and R2 are independently selected from H, Cl, COOH or CH3.
[0077] In one of the embodiments, the solvent may be ethanol, deionized water, or a combination thereof.
[0078] The following examples illustrate the present invention and are not intended to limit the present invention.
[0079] Examples
[0080] Example 1 - Materials and Methods
[0081] Material
[0082] All chemicals were purchased from commercial suppliers and used without any further purification, including phenazine (PZ, Aldrich), benzoquinone (Aldrich), 1,2-phenylenediamine (Aldrich), and 2,5-dihydroxy-1,4-benzoquinone (Aldrich), PTFE (Macklin), isopropyl alcohol (Macklin), potassium hydroxide (KOH, Aldrich), lithium hydroxide (LiOH, Macklin), Ketjen black (KB, ECP-600JD, Lion Corporation), isopropanol alcohol (Aldrich), Pt / C (20 wt. % in Pt, Macklin), (methyl sulfoxide)-d6 (DMSO-d6, Aldrich), Nafion D-520 dispersion (5% w / w in water and 1-propanol, Alfa Aesar), and 1,2-diaminobenzene (Aldrich). Aesar); and graphite oxide dispersion liquid (GO, 10 mg / g, GaoxiTech). Phenazine derivatives of 2-hydroxyphenazine (PZ-OH) and 1,2-dihydroxyphenazine (PZ-2OH) were prepared according to the following steps.
[0083] Electrochemical measurement methods for batteries
[0084] The cycling performance and electrochemical characteristics of the battery were characterized by a LAND CT2001A device and an electrochemical workstation CHI 760D at 25°C. The above electrochemical characteristics were measured at 25°C. The low-temperature performance of the PZ-2OH||Ni(OH)2 battery was tested in a low-temperature box (-30 to 20°C). All current densities, specific capacities, and energy densities in this work are calculated based on the mass of the phenazine derivative anode material. All batteries were tested at 0.2A g in the initial three cycles. -1 For each electrochemical test, at least three coin cells were assembled for testing.
[0085] Calculation of energy density and power density
[0086] Energy density of battery E (W h kg -1 ) and power density P(W kg -1 ) value is calculated as follows: where I is the applied current (A), V is the potential of the device (V), t is the discharge time (seconds), and m is the weight of the electrode (g).
[0087] Calculation of capacitance contribution
[0088] Ion and electron transport kinetics and capacitance contributions were calculated according to the following equations: i=kv b (4), Where k and b are constants. The above equation can be rearranged as follows: log(i)=log(k)+b*log(v) (5), By linearly plotting log(i) against log(v), the value of b can be obtained.
[0089] Example 2 - Preparation of 2-hydroxyphenazine (PZ-OH) and 1,2-dihydroxyphenazine (PZ-2OH)
[0090] Three types of phenazine derivatives (PZ, PZ-OH, and PZ-2OH) were successfully synthesized using a simple and environmentally friendly condensation method using low-cost diaminobenzene and quinone as precursors.
[0091] Synthesis of PZ-OH
[0092] First, 1.08 g of benzoquinone (10 mmol) was added to 100 mL of anhydrous alcohol solution to form solution A. Then, 1.08 g of 1,2-phenylenediamine (10 mmol) was added dropwise to solution A at -10°C and stirred continuously for 2 hours. The resulting mixture was then concentrated to 10 mL under reduced pressure, and 50 mL of deionized water was poured into the concentrated mixture. The resulting suspension was filtered and washed with deionized water until the filtrate became colorless. The yield of PZ-OH was approximately 70%.
[0093] Synthesis of PZ-2OH
[0094] First, 0.71 g of 2,5-dihydroxy-1,4-benzoquinone (0.51 mmol) and 130 mL of DI water were mixed in a round-bottom flask under a nitrogen atmosphere to form Solution A at 80°C. Then, 0.5 g of 1,2-phenylenediamine (0.46 mmol) was added dropwise to Solution A and stirred continuously for 7 hours. The mixture was then allowed to cool naturally to room temperature and stirred overnight. The resulting suspension was filtered and washed with deionized water until the filtrate became colorless. The yield of PZ-OH was approximately 80%.
[0095] Example 3 - Characterization of Synthesized PZ, PZ-OH and PZ-2OH
[0096] The chemical structures of these phenazine derivatives are Figure 1A As shown in , and by H NMR spectroscopy ( 1 The results were confirmed by H NMR) and Fourier transform infrared spectroscopy (FT-IR). 1 H NMR. Fourier transform infrared spectroscopy (FT-IR) was performed on a PerkinElmer Spectrum II spectrometer to characterize changes in specific chemical groups.
[0097] refer to Figure 1B , 1H NMR spectrum showed significant chemical shifts for PZ-OH (300 MHz, DMSO-d6) at 10.95 (s, 1H), 8.19 (dd, J = 8.7, 1.5 Hz, 1H), 8.13 (dd, 1H), 7.90 (ddd, J = 8.6, 6.6, 1.7 Hz, 1H), 7.83 (ddd, J = 8.2, 6.6, 1.6 Hz, 1H), 7.60 (dd, J = 9.4, 2.6 Hz, 1H), 7.35 ppm (d, J = 2.6 Hz, 1H) ( Figure 2A ); and for and PZ-2OH (300 MHz, DMSO-d6) at significant chemical shifts: 10.99 (s, 2H), 8.07 (s, 2H), 7.74 (s, 2H), 7.30 ppm (s, 2H) ( Figure 2B ). This indicates that PZ-OH and PZ-2OH were successfully synthesized.
[0098] The synthesized structure was further characterized by FT-IR ( Figure 1C ). In the FTIR spectrum of phenazine derivatives, the -1 、1518cm -1 、1145cm -1 and 827cm -1 The absorption peaks at around 3500 cm indicate the formation of C=N, C=C and C-H bonds, while the absorption peaks of PZ-OH and PZ-2OH at around 3500 cm -1 The broad FTIR spectrum at 400 nm confirmed the presence of hydroxyl groups.
[0099] Go to Figure 3A , the powder X-ray diffraction pattern (XRD) was also tested. An X-ray diffractometer device (XRD; Bruker, D2 Avance) was used to record the XRD curve. The results showed that the phenazine-based organic matter had a relatively ordered aggregation structure due to the π-π stacking of the molecules based solely on the phenazine derivatives. At the same time, the prepared phenazine derivatives showed different body colors, ranging from yellow for PZ to brown for PZ-OH, and finally to gray for PZ-2OH ( Figure 3B ).
[0100] In addition, the morphology and microstructure were observed by scanning electron microscopy (SEM; SU4800, Hitachi). The SEM images showed that PZ had a nanorod morphology with a length of about 300 μm, PZ-OH had a nanocluster morphology with a size of about 10 μm, and PZ-2OH had a nanorod morphology with a size of about 3 μm ( Figure 3C ).
[0101] Thermogravimetric analysis (TGA) was performed on a TG / DTA 6300 to obtain the thermodynamic stability of the materials, and the temperature was set at 5 °C min under N2. -1 The heating rate is from room temperature to 500℃. Figure 4 As the number of hydroxyl groups increases, the decomposition temperature gradually increases from 240°C (PZ) to 253°C (PZ-OH), and then to 308°C (PZ-2OH), indicating that the introduction of hydroxyl groups contributes to the thermal stability of organic materials. These results indicate that the substituents have a significant effect on the physical properties and electronic structure of these phenazine derivatives.
[0102] In order to further analyze the structure and reaction sites, density functional theory (DFT) calculations were used to simulate the molecular electrostatic potential (ESP). All DFT simulations were performed by the Gaussian 16 software package. The structure and energy levels of the highest occupied molecular orbital (HOMO) / lowest unoccupied molecular orbital (LUMO) of the phenazine derivatives were fully optimized at the B3LYP / 6-31+G (d, p) level. The molecular electrostatic potential results were performed using the Multiwfn 3.3.9 program, and the ESP diagrams were visualized using Visual Molecule Dynamics (VMD) software. Electron affinity is defined by the change in free energy between a neutral system and a negatively charged system.
[0103] At the van der Waals surface of the phenazine derivative molecule ( Figure 1A ), molecules with more negative ESP show a tendency towards electrophilic reactions 22 Results from ESP mapping revealed that the regions of the C=N bonds in the three phenazine derivatives (PZ, PZ-OH, PZ-2OH) exhibited negative ESP values, indicating that these regions were identified as highly reactive sites.
[0104] Example 4 - Electrochemical Measurements
[0105] A CR2032 coin cell was assembled in air for electrochemical measurements of phenazine derivatives. The anode was prepared by uniformly dispersing phenazine derivative powder, Ketjen black (KB), and polytetrafluoroethylene (PTFE) binder in a mass ratio of 6:2.5:1.5. The mixture was then mixed with a certain amount of isopropyl alcohol solvent and compressed onto nickel foam. The mixture was then vacuum-dried at 60°C overnight, resulting in a mass loading of 1-1.5 mg cm. -2 200 μL of an aqueous electrolyte containing 6 M KOH + 1 M LiOH was used as the electrolyte.
[0106] Regarding phenazine derivative||Ni(OH)2 batteries, excess Ni(OH)2 is used as the cathode, and the Ni(OH)2 electrode is obtained from a commercial nickel-metal hydride (Ni-MH) battery, which can eliminate the influence of the cathode material on the electrochemical performance of the full battery.
[0107] For organic||air batteries, a Pt / C cathode was prepared by blending 5 mg of Pt / C with 50 μL of Nafion solution (5 wt% Nafion in a 1:1 volume ratio of isopropanol to water). The mixture was sonicated for 30 minutes, and the resulting slurry was cast onto clean carbon cloth. The cathode was then dried in a vacuum oven at 80°C for 12 hours.
[0108] For the full cell assembly, a self-supporting graphene oxide (GO) membrane was inserted between the anode and the separator to prevent the dissolution of the anode material. The GO membrane was prepared using a simple filtration method. First, 1 g of GO aqueous solution was dispersed in 40 mL of ethanol and ultrasonicated for 60 minutes. The resulting suspension was then filtered and dried at 70 ° C for 24 hours. Finally, a mass of 0.6 mg cm was obtained after peeling the GO membrane from the filter paper. -2 Free-standing GO membrane.
[0109] In the three-electrode system, phenazine derivatives, Pt metal, and Hg / HgO were used as the working electrode, counter electrode, and reference electrode, respectively.
[0110] The electrochemical performance of the synthesized PZ, PZ-OH and PZ-2OH was evaluated in 6 M KOH aqueous alkaline electrolyte. Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) curves were performed on an electrochemical workstation (CHI 760E). Figure 1D , three phenazine derivatives at 5 mV s -1 The CV curves at a scan rate of 100 nm showed that the oxidation and reduction potentials decreased significantly after the introduction of hydroxyl groups. The reduction potentials of PZ, PZ-OH, and PZ-2OH dropped sharply from -0.78 V to -0.9 V, and then dropped to -1.07 V, respectively. The constant current charge / discharge (GCD) test, rate performance, and cycle performance were measured on a battery test system (LAND CT2001A). The above results are consistent with the GCD curves, which show that the average discharge voltage of phenazine derivatives decreases from PZ, PZ-OH to PZ-2OH ( Figure 1E However, the capacities of the three phenazine derivatives did not change significantly at 0.5 A g -1 The current density is about 160 mAh g -1 .
[0111] To understand the potential properties, the electron affinities of three phenazine derivatives were analyzed using first-principles DFT methods using B3LYP. Electron affinity represents the free energy change between a neutral system and a negatively charged system.
[0112] refer to Figure 1F , the redox potential shows a linear correlation with both the electron affinity and the LUMO energy level. Figure 1F It is shown that an increase in the number of hydroxyl groups generally leads to a decrease in electron affinity and a decrease in redox potential. The different redox potentials of the three phenazine derivatives are explained using the LUMO energy level ( Figure 5 A summary of the free energies of the neutral and charged systems and the calculated electron affinities (EA) of PZ, PZ-OH, and PZ-2OH are shown in Table 1. These results indicate that the high potential of molecular electrode materials can be predicted by more negative electron affinities and lower LUMO energy levels. 24,25 .
[0113] Table 1
[0114] More importantly, in aqueous alkaline electrolytes, the discharge potential of PZ-2OH is lower than that of reported organic anodes, such as 1,2-naphthoquinone (1,2-NQ), poly(anthraquinone-based sulfide) (PAQS), poly(2-vinylanthraquinone) (PVAQ), poly(1,4-anthraquinone) (P14AQ) ( Figure 1G and Table 2 ).
[0115] Table 2 Organic anode Discharge potential (V, relative to SHE) 1,2-NQ -0.44 PAQS -0.60 PVAQ -0.63 P14AQ -0.70 PZ -0.68 PZ-OH -0.80 PZ-2OH -0.98
[0116] Example 5 - Effect of the number of hydroxide groups on electrochemical performance
[0117] To investigate the effect of hydroxyl groups on the electrochemical performance, the effects of hydroxyl groups on the electrochemical properties of phenazine were explored, which revealed a structure-electrochemical activity correlation. -1 Up to 40mA g -1 The rate performance of three phenazine derivatives was tested in the current density range. Figure 6A The hydroxide-rich PZ-OH and PZ-2OH exhibited rate performance superior to that of PZ, especially at high current densities. -1 When the capacity of PZ-2OH and PZ-OH is maintained at 50 mAh g -1 , which retains 20% of the initial capacity, while the capacity of PZ is only 20 mAh g -1 .
[0118] To further understand the effect of hydroxy-substituted phenazine on the rate performance, electrochemical impedance spectroscopy (EIS) was used to analyze the electrochemical kinetic mechanism. Since all three electrodes were in the same electrolyte, the impedance caused by the diffusion process could be ignored. The effect on the rate performance was mainly attributed to the differences in the charge transfer process controlled by the electrochemical reaction steps.
[0119] As Figure 6B shown, the electrochemical system can be simplified to the co-control of ohmic impedance and charge transfer impedance, which can be intuitively measured by the EIS of different electrodes. As shown in the Nyquist plot, the ohmic impedance of PZ-2OH is less than that of PZ-OH and PZ ( Figure 6C ), which is consistent with the difference in the highest occupied molecular orbital (HOMO)-LUMO energy levels (PZ-2OH (ΔE = 3.52 eV) < PZ-OH (ΔE = 3.57 eV) < PZ (ΔE = 3.66 eV)) ( Figure 5 ). The low HOMO-LUMO energy gap indicates that electrons can easily transition from the highest occupied orbital to the lowest occupied orbital 23 . Therefore, the relatively high conductivity (smaller ohmic impedance) of PZ-2OH contributes to the high rate performance.
[0120] In addition, by quantitatively analyzing the real part (Z′) of the impedance, the ion diffusion resistance (σ) was obtained, and the ion diffusion resistance is linear with the reciprocal of the square root of the frequency (ω<00X0077>). The smaller the slope of the linear trend indicates the faster the ion transport. Referring to Figure 6D , the PZ-2OH electrode produced the lowest σ value of 11.11 Ωs -0.5 , followed by PZ-OH producing the lowest σ value (36.08 Ωs -0.5 ) and PZ producing the lowest σ value (57.88 Ωs<00X0081>), which indicates that the PZ-2OH anode has faster ion transport kinetics (lower charge transfer impedance).
[0121] Furthermore, the charge transfer behavior was further evaluated by the activation energy (Ea). E a was calculated from the EIS spectra at different temperatures, and it can be calculated by the following equation: 1 / R ct = A0 e -Ea / RT , where R ct , R, and T represent the charge transfer resistance (Ω), the gas constant (8.314 J mol -1 K -1 ), and the test temperature (298 K), respectively.
[0122] According to the Arrhenius equation, the Ea value of PZ-2OH is 3.99 kJ mol -1 ( Figure 6E and Figure 7 ), which is less than PZ-OH (4.57 kJ mol -1 ) and PZ (5.15 kJ mol -1 ), which proves that the introduction of hydroxyl groups ensures fast ion diffusion and efficient charge transport.
[0123] In addition, by using the 1mV s -1 to 10mVs -1 The reaction kinetics studied by CV tests at a scan rate range also demonstrated the excellent rate performance of the PZ-2OH anode. The b values obtained from the oxidation and reduction peak currents of PZ, PZ-OH, and PZ-2OH were (0.68, 0.54), (0.60, 0.57), and (0.84, 0.71), respectively. Figure 8-10 These values are determined based on the relationship between scan rate (v) and peak current (i). Figure 8 shows the 1mV s -1 , 2mV s -1 , 4mV s -1 , 6mV s -1 , 8mV s -1 and 10mV s -1 CV curves at scan rates of , and the corresponding logarithms of PZ, PZ-OH, and PZ-2OH peak Relative to log v. The upper line represents the reduction peak, and the lower red line represents the oxidation peak. Figure 9 The capacitance contributions of PZ, PZ-OH, and PZ-2OH at different scan rates are shown. Figure 10 The coefficients b for PZ, PZ-OH, and PZ-2OH are shown. (A b value of 0.5 indicates a diffusion process, while a b value of 1.0 indicates a capacitive process.) The results clearly indicate that the redox processes of the three phenazine derivatives exhibit both ion diffusion and capacitive behavior. Notably, the diffusion behavior shows a gradual increase from PZ to PZ-OH, and further increases to PZ-2OH, as shown in FIG. Figure 10 As shown in .
[0124] According to the above analysis, it can be found that the ion diffusion kinetics of the phenazine derivative electrode is affected by the hydroxyl group, which can be used to increase the possibility of hydration by forming intramolecular / intermolecular hydrogen bonds, such as Figure 6F As shown in . Due to the steric hindrance of the neighboring H atoms, PZ shows a lower hydration trend compared to PZ-OH and PZ-2OH 20The presence of hydrogen bonds facilitates charge transfer, which results in low ohmic impedance (due to high electrical conductivity) and low charge transfer impedance (due to ion channels formed through the hydrogen bond network). These factors contribute to the system's exceptional high-rate performance.
[0125] The hydrogen bond interactions were further confirmed by the calculated reduced density gradient (RDG) and the corresponding gradient isosurface plots, as shown in Figure 6G Specifically, the detected green peak in sign (λ2)ρ from -0.02 arbitrary units to 0.00 arbitrary units demonstrates the weak interaction between PZ-2OH molecules.
[0126] Example 6—PZ-2OH| | Ni(OH) 2 Electrochemical performance of batteries
[0127] The electrochemical performance of PZ-2OH||Ni(OH)2 full cells was evaluated using 6M KOH and 1M LiOH aqueous electrolytes. + ions effectively suppress O2 evolution.
[0128] refer to Figure 11 A 5-micron-thick graphite oxide (GO) membrane is inserted between the anode and the separator. This GO membrane acts as a strong barrier, effectively preventing the anode from dissolving. The membrane weighs about 0.67 mg cm -2 In addition, a GO||Ni(OH)2 full cell was assembled to verify the capacity contribution of the inserted GO membrane. Both CV images and GCD images confirmed that the GO membrane showed a negligible contribution to the full cell capacity ( Figures 12A-12B ).
[0129] Go to Figure 13A The typical CV curve of the PZ-2OH||Ni(OH)2 full cell shows an oxidation peak at approximately 1.61 V and a reduction peak at 1.47 V, which is caused by the redox reaction of the Ni(OH)2 cathode and the PZ-2OH anode. Such a high discharge potential of the PZ-2OH||Ni(OH)2 battery is superior to that of the previously reported Cd||Ni and MH||Ni batteries. 2,9 Furthermore, the green and cost-effective preparation method provides PZ-2OH with a significant price advantage over other anode materials in alkaline aqueous batteries, such as Figure 14 As shown in .
[0130] Figure 13B and Figure 15A The results show that the PZ-2OH||Ni(OH)2 battery has a different current density (0.2A g -1, 0.5A g -1 、1A g -1 、2A g -1 、5A g -1 and 10A g -1 ) under the charge / discharge spectrum and rate performance. Full battery test proved that at 0.2A g -1 At a current density of 178 mAh g -1 High discharge capacity (based on the mass of PZ-2OH) and high -1 64mAhg -1 In addition, when the current density is restored to 0.2Ag -1 When the discharge capacity is restored to 170 mAh g -1 , which demonstrates the excellent reversibility. The high capacity and fast diffusion rate of the PZ-2OH anode material provide excellent power density (at 10 A g -1 The following is 26.2KW kg -1 ) and energy density (at 0.2A g -1 The following is 247Wh kg -1 )( Figure 13C The high power density makes it close to supercapacitors with fast charging behavior, while the high energy density also surpasses previously studied lead-acid batteries and nickel-based batteries.
[0131] Furthermore, the discharge voltage of the full cell is higher than that of the organic-based cell among various aqueous electrolytes, including acidic electrolytes (organic pyrene-4,5,9,10-tetraone||MnO2(PTO||MnO2) 26 , Pb||tetrachlorobenzoquinone / reduced graphene oxide (Pb||PCHL-rGO) 27 , all-organic protons 28 ), mild electrolyte (Zn||tetraamino-p-benzoquinone (Zn||TABQ) 29 、KMnHCF||3,4,9,10-perylenetetracarboxylic diimide (KMnHCF||PTCDI) 30 、Mn||tetrachloro-1,4-benzoquinone (Mn||4-Cl-BQ) 31 ) and alkaline electrolyte ((P14AQ||Ni(OH)2) 32 、(PAQS||Ni(OH)2) 34 ) of the reported discharge voltage ( Figure 13D ).
[0132] The excellent rate performance of the PZ-2OH||Ni(OH)2 battery is mainly attributed to its fast kinetics, which was studied by CV tests at different scan rates ( Figure 15B and 16 The PZ-2OH||Ni(OH)2 cell exhibits slopes of 0.84 and 0.91 during the reduction and oxidation processes, respectively. These values indicate the dominance of pseudocapacitive behavior in the cell.
[0133] Figure 13E The results show that the PZ-2OH||Ni(OH)2 full battery has a temperature range of -30℃ to 20℃ and a -1 GCD curves at current densities of 100 nm and 100 nm, respectively. Due to the high concentration of alkaline electrolyte and the high electrochemical kinetics of the organic electrode, the PZ-2OH||Ni(OH)2 battery can operate at -30°C and maintain 73% capacity.
[0134] The PZ-2OH||Ni(OH)2 battery was also tested at 0.5A g -1 Under the cycle of 1000 cycles, the battery has a long-lasting cycle performance of more than 9000 cycles, and during the entire cycle process, the average capacity loss rate per cycle is about 0.075%. ( Figure 13F ).
[0135] Figure 13G The comprehensive performance evaluation between conventional Ni-based batteries (Zn||Ni, MH||Ni, Cd||Ni) and PZ-2OH||Ni(OH)2 is shown, including price, energy density, voltage, toxicity and stability. Therefore, PZ-2OH||Ni(OH)2 has significant advantages over conventional Ni-based batteries. The price is calculated based on the anode material; and the non-toxicity index is rated from 1 to 5, with smaller non-toxicity data indicating greater toxicity. Table 3 is a comparison of the comprehensive performance of commercial alkaline nickel-based batteries. PZ-OH is cheaper than alloys, less toxic than cadmium metal, and more stable than Zn metal, demonstrating its comprehensive performance advantages in price, toxicity, stability and energy density.
[0136] Table 3
[0137] Considering that the electrolyte of 6M KOH+1M LiOH contains three cationic species (K + 、Li + and H + ), so inductively coupled plasma emission spectrometry (ICP) measurements were performed to identify the charge carrier species in the PZ-2OH anode 21According to Table 4, although lithium and potassium signals appeared, the contents of these elements before and after charging and discharging did not change significantly before and after cycling, which indicates that K + He Li + are probably not charge carriers. The detected lithium and potassium signals are probably the remnants of the electrolyte on the electrode material. Therefore, the charge carriers in the PZ-2OH anode are more likely to be H +20,22,33,34 .
[0138] Table 4
[0139] To explore the charge storage mechanism, ex situ XPS and in situ Raman measurements were used to analyze the structural changes of the PZ-2OH electrode in the labeled state during charge-discharge. X-ray photoelectron spectroscopy (XPS; ESCALAB 250) was performed to analyze the surface composition. Raman spectroscopy was performed on a WITec alpha300 access equipped with a 532 nm laser to record the changes in chemical bonds during the charge / discharge reaction. The content of metal ions (lithium and potassium) was determined by inductively coupled plasma optical emission spectrometry (ICP-MS: Agilent 7700s (Agilent 7700s), ICP-OES: Agilent 720).
[0140] refer to Figure 17A , ex situ XPS spectroscopy reveals the ion coordination / dissociation mechanism of the PZ-2OH anode in the original, fully charged, and fully discharged states. In the XPS spectra of the electrode in the charged / discharged state, no signals from the sodium and lithium elements were observed, such as Figure 17B This further proves that the coordination ion is H + In the high-resolution N1s spectrum, a clear shift of the binding energy of the N peak toward the low energy region was observed when charged to 1.6 V. Subsequently, after discharge, the binding energy returned to the high energy region. This observation suggests that the -C=N bond gained electrons during the charging process and underwent reduction to form a -CN bond, as shown in Figure 17C Conversely, during discharge, the -CN bond loses electrons and is oxidized back to a C=N bond, as indicated by previous studies. 22 These findings are consistent with observations from in situ Raman spectroscopy ( Figure 17D ). In addition, the characteristic shift of the Raman peak corresponding to the C=N bond further supports this behavior, such as Figure 17E The 1678 cm-1 corresponding to C=N stretching -1 The absorption peak at 17It weakened significantly and finally disappeared after the battery was charged to 1.6 V. When the battery was discharged to 0.8 V, the reverse evolution was observed, indicating that the coordination / intercoordination behavior exhibited high reversibility.
[0141] By combining the results from EDX, ex situ XPS, and in situ Raman characterization, the charge / discharge storage behavior of PZ-2OH is based on the n-type doping reaction, e.g. Figure 18 During the initial charging process, the PZ-2OH anode undergoes reduction by accepting delocalized electrons, thereby forming negative radicals. + Ions are inserted into the PZ-2OH to maintain electrical neutrality. During the subsequent charge process, the negatively charged PZ-2OH anode is then reduced back to its neutral state by releasing electrons.
[0142] In addition, the reduction state of the PZ-2OH anode was monitored by ex situ FTIR after different cycles ( Figure 17F ). Except for slight changes in the initial few cycles, no obvious chemical decomposition was detected, indicating good chemical stability in strongly alkaline solution, which ensures a low capacity decay rate during long cycling.
[0143] In order to further verify the adaptability of PZ-2OH under alkaline conditions, a PZ-2OH||air full battery was assembled. The GCD curve and rate performance of the PZ-2OH||air battery are shown in Figure 19A and 19B Go to Figure 20 The CV curves of the PZ-2OH||air full cell show typical oxidation and reduction peaks at 0.8 V and 1.5 V, which confirms that PZ-2OH can be used as the anode of the air battery cell under alkaline conditions. The battery cell shows a high charge / discharge rate at 0.2 A g based on the mass of PZ-2OH. -1 , 0.5A g -1 、1A g -1 、2A g -1 、5A g -1 and 10A g -1 181.3mAh g -1 、158.9mAh g -1 、136.7mAh g -1 、104.2mAh g -1 , 72.9mAh g -1 and 52.3mAh g -1 The specific capacity indicates excellent rate performance. It is worth noting that the rate performance observed in the PZ-2OH||air full cell is relatively lower than that in the PZ-2OH half cell ( Figure 6A). This difference can be attributed to the limited catalytic activity of the air cathode under high current conditions.
[0144] Furthermore, the cycling performance of the PZ-2OH||Air full battery shows a high capacity retention of approximately 65.8% over the initial 400 cycles, as shown in Figure 2. Figure 19C As shown in Figure 2, the capacity decreases significantly as the cycle continues, which is caused by the loss of electrolyte in the open system. The capacity is immediately restored after the electrolyte is refilled into the battery, indicating that the capacity decay is mainly related to the loss of electrolyte and the reduction of ion transport. After 1000 cycles, the capacity of the full battery remains at 80.4 mAh g -1 The obtained results provide convincing evidence that the developed PZ-2OH materials function effectively in alkaline electrolytes. Such materials show great potential for application in various alkaline batteries, enabling them to offer superior energy density / power density and rate performance.
[0145] In summary, the present invention presents a single-step, efficient, environmentally friendly and cost-effective preparation method for a series of phenazine derivatives. These derivatives are synthesized by using quinone derivatives and phenylenediamine derivatives as reaction precursors and ethanol and / or water as dispersion media. Three phenazine derivatives, namely phenazine (PZ), 2-hydroxyphenazine (PZ-OH) and 1,2-dihydroxyphenazine (PZ-2OH), contain different numbers of hydroxyl groups. The three phenazine derivatives are used as model compounds to study the effect of grafted functional groups on the electrochemical redox properties of phenazine as anode material in alkaline batteries. For alkaline nickel-based batteries, the cathode material used is commercial nickel hydroxide (Ni(OH)2), and for alkaline air batteries, it is Pt / C. The optimized PZ-2OH||Ni(OH)2 battery can exhibit 208mAh g -1 High capacity (anode), 247Wh kg -1 High energy density (anode), at 10A g -1 26.2KW kg -1 The battery features high power density, excellent cycling stability of over 9000 cycles and a low capacity decay rate of approximately 0.075% per cycle.
[0146] definition
[0147] Throughout this specification, unless the context requires otherwise, the word "comprise" or variations such as "comprises" or "comprising" should be understood to imply the inclusion of a stated integer or group of integers, but not the exclusion of any other integer or group of integers. It should also be noted that in this disclosure and particularly in the claims and / or paragraphs, terms such as "comprises," "comprised," "comprising," etc. may have the meaning ascribed to them in U.S. patent law; for example, it allows for elements not expressly recited, but excludes elements present in the prior art or elements that affect the basic or novel characteristics of the invention.
[0148] Furthermore, throughout this specification and claims, unless the context requires otherwise, the word "include" or variations such as "includes" or "including", will be understood to imply the inclusion of a stated integer or group of integers but not the exclusion of any other integer or group of integers.
[0149] References in this specification to "one embodiment," "an embodiment," "an example embodiment," etc., indicate that the described embodiment may include a particular feature, structure, or characteristic, but not every embodiment will necessarily include the particular feature, structure, or characteristic. Furthermore, such phrases do not necessarily refer to the same embodiment. Furthermore, when a particular feature, structure, or characteristic is described in conjunction with an embodiment, it is understood that it is within the knowledge of those skilled in the art to be able to incorporate such feature, structure, or characteristic in conjunction with other embodiments, whether or not explicitly described.
[0150] Other definitions of selected terms used in this article may be found in the detailed description of the present invention and are applicable throughout the text. Unless otherwise defined, all other technical terms used in this article have the same meaning as commonly understood by those of ordinary skill in the art to which the present invention belongs.
[0151] Those skilled in the art will appreciate that, in light of these teachings, alternative embodiments may be implemented without undue experimentation or without departing from the spirit or scope of the invention as set forth in the appended claims. The present invention is limited solely by the following claims, which when considered in conjunction with the above description and drawings are intended to encompass all such embodiments and modifications.
[0152] Industrial Applicability:
[0153] According to MarketsandMarkets TMAccording to a new market research report, the market for electrode materials is expected to grow from $25.9 billion in 2022 to $52.6 billion in 2027. Organic materials are preferred over traditional inorganic materials due to their environmental friendliness, sustainability, flexible structural design, and abundance in the Earth's crust. The structural diversity of organic materials also allows for battery modification and innovation.
[0154] In the present invention, a series of phenazine derivatives with different types and numbers of side substituents are prepared using a simple and environmentally friendly condensation method. By adjusting the electron donating / electron withdrawing ability of these side groups, the organic anode can be customized to achieve the desired electrochemical performance. The developed organic phenazine derivatives have a wide range of applications in alkaline battery systems, including alkaline nickel-based batteries and alkaline air batteries. These advances have greatly promoted the development of alkaline aqueous batteries. The developed organic phenazine materials exhibit ultra-low redox potential and extremely high cycle stability. Their low cost, simple preparation method, environmentally friendly properties and excellent electrochemical performance make them very promising in large-scale stationary energy storage, portable high-energy devices and high-safety energy storage systems.
[0155] References: The disclosures of the following references are incorporated by reference 1. J. F. Parker, C. N. Hervin, I. R. Pala, M. Machler, M. F. Burz, J. W. Long, and D. R. Rolison, Science, 2017, 356, 415-418. 2. T. Sakai, I. Uehara and H. Ishikawa, J. Alloy Comp., 1999, 293, 762-769. 3. T.J. Sun, C. Liu, J.Y. Wang, Q.S. Nian, Y.Z. Feng, Y. Zhang, Z.L. Tao, and J. Chen, Nano Res., 2020, 13, 676-683. 4. W. Zhou, D. Zhu, J. He, J. Li, H. Chen, Y. Chen, and D. Chao, Energy Environ Sci., 2020, 13, 4157-4167. 5. F. Wang, J. Xie, D. Zheng, F. Yang, H. Zhang and X. Lu, Advanced Materials, 2022, 34, 2200085. 6. L. Jiang, D. Dong, and Y.-C. Lu, Nano Res. Energy, 2022, 1, e9120003. 7. S. Chen, T. Wang, L. Ma, B. Zhou, J. Wu, D. Zhu, Y. Y. Li, J. Fan, and C. Zhi, Chemistry, 2022. 8. MJ D′Ambrose, D.E. Turney, G.G. Yadav, M. Nyce and S. Banerjee, ACS Appl. Energy Mater., 2021, 4, 3381-3392. 9. F. Feng, M. Geng and D. Northwood, Int. J. Hydrogen Energy, 2001, 26, 725-734. 10. S. Chen, C. Peng, D. Xue, L. Ma, and C. Zhi, Angew. Chem., 2022, 134, e202212767. 11. J. S. Ko, A. B. Geltmacher, B. J. Hopkins, D. R. Rolison, J. W. Long, and J. F. Parker, ACS Applied Energy Materials, 2018, 2, 212-216. 12. S. Yang, H. Lv, Y. Wang, X. Guo, L. Zhao, H. Li and C. Zhi, Angew. Chem. Int. Ed., 2022, 61, e202209794. 13. J. Kim, S. Ko, C. Noh, H. Kim, S. Lee, D. Kim, H. Park, G. Kwon, G. Son, and J. W. Ko, Angewandte Chemie, 2019, 131, 16920-16925. 14. G. Liang, X. Li, Y. Wang, S. Yang, Z. Huang, Q. Yang, D. Wang, B. Dong, M. Zhu, and C. Zhi, Nano Research Energy, 2022, 1, e9120002. 15. C. Luo, O. Borodin, X. Ji, S. Hou, K. J. Gaskell, X. Fan, J. Chen, T. Deng, R. Wang, and J. Jiang, Proceedings of the National Academy of Sciences of the United States of America (Proc. Nat. Acad. Sci.), 2018, 115, 2004–2009. 16. H. Cui, L. Ma, Z. Huang, Z. Chen, and C. Zhi, Smart Materials (SmartMat), 2022. 17. S. Zhang, S. Long, H. Li and Q. Xu, Chem. Eng. J., 2020, 400, 125898. 18. Q. Wang, Y. Liu, and P. Chen, J. Power Sources, 2020, 468, 228401. 19. G. Dai, Y. Liu, Z. Niu, P. He, Y. Zhao, X. Zhang and H. Zhou, "Matter", 2019, 1, 945-958. 20. A. Hollas, X. Wei, V. Murugesan, Z. Nie, B. Li, D. Reed, J. Liu, V. Sprenkle, and W. Wang, Nature Energy, 2018, 3, 508–514. 21. C. Zhang, W. Ma, C. Han, L.-W. Luo, A. Daniyar, S. Xiang, X. Wu, X. Ji, and J.-X. Jiang, Energy and Environmental Science, 2021, 14, 462-472. 22. Z. Tie, L. Liu, S. Deng, D. Zhao and Z. Niu, Chinese Journal of Applied Chemistry, 2020, 132, 4950-4954. 23. L. Ma, S. Chen, D. Wang, Q. Yang, F. Mo, G. Liang, N. Li, H. Zhang, J. A. Zapien, and C. Zhi, Advanced Energy Mater., 2019, 9, 1803046. 24. K. C. Kim, T. Liu, S. W. Lee, and S. S. Jang, Journal of the American Chemical Society (J. Am. Chem. Soc.), 2016, 138, 2374-2382. 25. T. Liu, K. C. Kim, B. Lee, Z. Chen, S. Noda, S. S. Jang, and S. W. Lee, Energy and Environmental Science, 2017, 10, 205-215. 26. Z. Guo, J. Huang, X. Dong, Y. Xia, L. Yan, Z. Wang, and Y. Wang, Nature Communications, 2020, 11, 1-9. 27. F. Yue, Z. Tie, S. Deng, S. Wang, M. Yang and Z. Niu, Angewandte Chemie International Edition, 2021, 60, 13882-13886. 28. R. Emanuelsson, M. Sterby, M. and M. Journal of the American Chemical Society, 2017, 139, 4828-4834. 29. Z. Lin, H.-Y. Shi, L. Lin, X. Yang, W. Wu, and X. Sun, Nature Communications, 2021, 12, 1-9. 30. L. Jiang, Y. Lu, C. Zhao, L. Liu, J. Zhang, Q. Zhang, X. Shen, J. Zhao, X. Yu, and H. Li, Nature Energy, 2019, 4, 495–503. 31. S. Bi, S. Wang, F. Yue, Z. Tie and Z. Niu, Nature Communications, 2021, 12, 6991. 32. C. Liu, T. Ma, K. Xia, X. Hou, Q. Nian, Y. Cai, and J. Liang, Sustainable Energy Fuels, 2020, 4, 132–137. 33. J. Xu, S. Pang, X. Wang, P. Wang, and Y. Ji, Joule, 2021, 5, 2437–2449. 34. S. Pang, X. Wang, P. Wang and Y. Ji, Angewandte Chemie International Edition, 2021, 60, 5289-5298.
Claims
1. An alkaline battery based on a phenazine derivative, comprising: an anode formed from a phenazine derivative having 1 to 4 pendant substituents; cathode; a separator disposed between the cathode and the anode; as well as an electrolyte disposed in a space between the cathode and the anode, The alkaline battery based on phenazine derivatives showed a high performance at 0.2 A g -1 At least 170mAh g -1 The reversible capacity at 10A g -1 At least 20KW kg -1 The power density is as high as 10000 cycles, and the cyclability is stable over 9000 cycles. 2 . The phenazine derivative-based alkaline battery according to claim 1 , wherein the side substituent comprises an electron donating group or an electron withdrawing group. 3 . The phenazine derivative-based alkaline battery according to claim 2 , wherein the electron donating group comprises an amino group, a hydroxyl group, or a combination thereof, or the electron withdrawing group comprises a methyl group, a carboxyl group, or a combination thereof. 4 . The phenazine derivative-based alkaline battery according to claim 1 , wherein the anode and the cathode comprise a current collector, at least one active material, one or more conductive particles, and at least one binder. 5 . The phenazine derivative-based alkaline battery according to claim 4 , wherein the current collector comprises carbon nanotube paper, carbon cloth and nickel foil.
6. The phenazine derivative-based alkaline battery according to claim 4, wherein the at least one active material comprises phenazine, 2-hydroxyphenazine and 1,2-dihydroxyphenazine.
7. The phenazine derivative-based alkaline battery according to claim 4, wherein the one or more conductive particles include carbon nanotubes, Ketjen black and super P.
8. The phenazine derivative-based alkaline battery according to claim 4, wherein the at least one binder comprises sodium carboxymethylcellulose, polyvinylidene fluoride, and polytetrafluoroethylene.
9. The phenazine derivative-based alkaline battery according to claim 1, wherein the cathode comprises Ni(OH)2 and Pt / C. 10 . The phenazine derivative-based alkaline battery according to claim 1 , wherein the electrolyte comprises a solvent and a solute, and the solvent comprises deionized water, and the solute comprises sodium hydroxide, potassium hydroxide, and lithium hydroxide. 11 . The phenazine derivative-based alkaline battery according to claim 10 , wherein the concentration of the solute is in the range of 1 M to 6 M.
12. The phenazine derivative-based alkaline battery according to claim 1, wherein the phenazine derivative-based alkaline battery further comprises a graphene oxide membrane, wherein the phenazine derivative-based alkaline battery is assembled by inserting the graphene oxide membrane between the anode and the separator, and the electrolyte is added between the anode and the cathode.
13. The alkaline battery based on phenazine derivatives according to claim 1, wherein the alkaline battery based on phenazine derivatives has a capacity of 40 mAh g -1 The high rate capacity retains at least 10% of the initial capacity, and the discharge potential of the phenazine derivative-based alkaline battery is lower than -0.8V.
14. The phenazine derivative based alkaline battery according to claim 2, wherein an increase in the number of electron donating side group substituents results in a decrease in electron affinity and a decrease in redox potential.
15. A method for preparing the phenazine derivative according to claim 1, the method comprising: preparing at least one precursor, the at least one precursor comprising at least one benzene derivative, at least one phenylenediamine derivative, and a solvent; dissolving the at least one benzene derivative in the solvent to form a uniform solution A; mixing the at least one phenylenediamine derivative with the solution A to form a suspension; as well as The suspension was filtered and washed with deionized water until the filtrate became colorless. The molar ratio of the at least one benzene derivative to the at least one phenylenediamine derivative is in the range of 1:1 to 1:0.
8.
16. The method according to claim 15, wherein the method further comprises concentrating the mixture under reduced pressure, and adding deionized water to obtain a suspension, followed by filtering and washing the suspension.
17. The method of claim 15, wherein the at least one benzene derivative comprises benzoquinone or 2,5-dihydroxy-1,4-benzoquinone.
18. The method of claim 15, wherein the at least one phenylenediamine derivative has the following chemical structure: wherein R1 and R2 are independently selected from H, Cl, COOH or CH3.
19. The method of claim 15, wherein the solvent comprises ethanol, deionized water, or a combination thereof.
20. The method according to claim 15, wherein the step of mixing the at least one phenylenediamine derivative with the solution A to form a suspension has a reaction temperature in the range of -10°C to 100°C, and a reaction time in the range of 5-10 hours.